2016
DOI: 10.1002/ajim.22656
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of safe work practices in logging in the southern United States

Abstract: Participants indicated high levels of personal motivation to work in a safe manner but tended to underestimate workplace hazards and expressed widely varying levels of co-worker trust. Am. J. Ind. Med. 60:58-68, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
3
19
0
3
Order By: Relevance
“…Similar outcomes were reported for a multi-year video-based safety training intervention program for West Virginia loggers [45]. Interestingly, Conway et al [22] reported that one important risk factor is human error, due to complacency, inattention, and/or underestimation of risks, and suggested that such error can be partially related to the repetitiveness of logging jobs and individual worker's motivation to work safely.…”
Section: Safety Concerns and Opinions Of Loggerssupporting
confidence: 60%
“…Similar outcomes were reported for a multi-year video-based safety training intervention program for West Virginia loggers [45]. Interestingly, Conway et al [22] reported that one important risk factor is human error, due to complacency, inattention, and/or underestimation of risks, and suggested that such error can be partially related to the repetitiveness of logging jobs and individual worker's motivation to work safely.…”
Section: Safety Concerns and Opinions Of Loggerssupporting
confidence: 60%
“…Finally, each secondary index was divided into a certain number of tertiary indicators of 95. The indices used to appraise the reliability of the Delphi survey mainly include numbers of consultations, numbers of panelists, representative of panelists, enthusiasm of panelists, authority as well as the consistent opinions of panelists [14,18,21]. In the present work, the respective description was presented as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the full consideration of the mechanisms and features of occupational hazards, the study aims to establish a comprehensive evaluation system for hazardous working environments from certain aspects, such as inherent occupational hazards, offset factors of occupational hazards and workers' health conditions. In addition, we collected data on advanced experience from domestic and foreign assessment involving workplace occupational hazards [17][18][19][20][21]. Ultimately, the study intends to focus on formulating a comprehensive, dynamic, objective, effective as well as scientific system to mirror the status on the prevention and control of occupational hazards in the iron and steel industry based on the modified Delphi technique.…”
Section: Introductionmentioning
confidence: 99%
“…The hazards of logging are well-documented in the literature; previous research has catalogued logging injuries and fatalities across the United States [10,11,15,16,18] and enumerated the factors that contribute to unsafe work environments [15,16,18,21,26,52]. Despite recognition of the risks, including by loggers themselves [18,26,52], high occupational fatality rates persist in the industry.…”
Section: Discussionmentioning
confidence: 99%